“Efectos de la dosis del herbicida (quisalofop p-tefurylo) en el control pos-emergente de malezas, en el rendimiento de caupi (vigna unguiculata L. WALP.), en el sector cantrocillo provincia de huallaga-Saposoa - Fonseca Alva, Paúl Nicolae (2014)
This research entitled "Effects of the herbicide dose (Quizalofop -P- Tefurylo) in the post-emergent weed control on the yield of cowpea in the Huallaga Province Cantarcillo sector (Vigna unguiculata L. Walp.) - Saposoa "was carried out in arder to assess and determine the effect of different doses of Quizalofop-P-tefurylo herbicide for post emergence weed control in the crop yield of cowpea sp. Statistical randomized complete block design with tour treatments and three replications. The treatments were TO (control), T1 (1,0 l.ha-1), T2 (0,75 l.ha -1) and T4 (0,5 l.ha-1). The results indicate. that: treatment ·T2~ (Quizalofop-f>"''~'tefurylo 1',ü l.ha-1)· readled· the highest average performance with 678,86 kg ha-1 statistically outperforming all other treatments, followed by treatments T3 (Quizalofop-P- tefurylo 0,75 l.ha-1), T1 (Control weeding manual) and T 4 (Quizalofop -P- tefurylo 0,5 l.ha-1) , who obtained average yields 667,20 kg ha-1, respectively. Treatments T1 (Control weeding manual) and T4 (Quizalofop-P- tefurylo 0,5 l.ha-1) with averages of 99 and 90% control monocot weeds yielded the best results, with excellent grades and economic control, determining a degree of abundance of weeds classified as thin and sparse, statistically outperforming T3 treatments (Quizalofop -P- tefurylo 0,75 l.ha-1) and T2 (Quizalofop-P- tefurylo 1.0 l.ha-1) • Treatments T1 (Control weeding manual) and T4 (Quizalofop-P- tefurylo 0,5 l.ha-1) with averages of 99 and 93 % control of dicotyledonous weeds were the best performers, with very good grades and good, determining a degree of weed abundance of thin and sparse, statistically outperforming T3 treatments (Quizalofop-P- tefurylo 0,75 1.ha-1) and T2 (Quizalofop - P- tefurylo 1,0 l.ha-1), respectively Keywords: Dry dose, effects, weed, cool, monocots, dicots, yield.